UPAYA MENGEMBANGKAN JIWA KEWIRAUSAHAAN IBU RUMAH TANGGA DI DESA ALASMALANG DALAM PENGEKSPLORASIAN REBUNG SEBAGAI KRIPIK - Hasan Muchtar Fauzi (Relawan Jurnal Indonesia, 2017)
In the modern era many women who have a profession is not inferior to her husband with a variety of reasons, especially in urban areas. Good for the purpose of helping to meet the needs of the household, until to seek its own satisfaction. But unlike the wives in the villages, the majority of them are housewives who rely solely on the salary or income of husbands to meet all household needs, which in fact the income of the husband has not been able to meet daily needs. For example in the village of Alasmalang, where the majority of mothers there are housewives, with low education level, so that not much knowledge owned, either in the form of skill or creativity is mastered to be able to help lift the family's economy. Therefore, we plan to provide training on making bamboo shoots in the hope that after following the training on making bamboo shoots into chip,especially housewives can get a job with entrepreneurship or create a working group. In the village of Alasmalang the potential with bamboo plants is quite high, because many farmers who planted land owned by bamboo plants. But only use the bamboo trees that are old enough, and the people around just know bamboo processed into vegetables or stir-fry bamboo shoots only. Therefore, this training is expected to become a new land for housewives to start entrepreneurship. Food fiber content in bamboo shoots is also quite good that is 2.56 percent, higher than other types of tropical vegetables, other than that bamboo shoots have a high enough potassium content. Potassium levels per 100 grams of bamboo shoots is 533 mg. Foods that potassium fiber, which is at least 400 mg, can reduce the risk of stroke.